2020
DOI: 10.1111/coa.13565
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on Transoral robotic surgery (TORS) for carcinoma of unknown primary origin: Has tongue base mucosectomy become indispensable?

Abstract: Background Transoral robotic surgery (TORS) is increasingly used in head and neck surgery and in carcinoma of unknown primary (CUP) origin specifically. Due to the rising incidence of human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (OPSCC), there is a rationale for finding ways to de‐escalate treatment strategies. This review aims to test the hypothesis that TORS is a meaningful adjunct in the diagnostic (and therapeutic) pathway in CUP in head and neck. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…This rate is comparable to 38% as reported by Nilsson et al 24 [24][25][26] A recent review on CUP-TORS reported an average identification of the primary tumor in 72% of cases (range 17%-90%), 55%-96% of these being HPV+ (vs. 42.1% HPV+ in our cohort). 27 The actual benefit of TORS for CUP is possible treatment deintensification by identifying/resecting the primary, as illustrated by Hatten et al 26 Sixty-seven percent of their CUP patients thus avoided chemotherapy and 25% avoided RT, thus reducing the risk of long-term dysphagia, carotid atherosclerosis, and xerostomia in a relatively young patient group. 26,27 Looking at all primarily treated SCC patients in our cohort, adjuvant (C)RT could be avoided in 48.9% of patients (treated with Xi-TORS only).…”
Section: Discussionmentioning
confidence: 99%
“…This rate is comparable to 38% as reported by Nilsson et al 24 [24][25][26] A recent review on CUP-TORS reported an average identification of the primary tumor in 72% of cases (range 17%-90%), 55%-96% of these being HPV+ (vs. 42.1% HPV+ in our cohort). 27 The actual benefit of TORS for CUP is possible treatment deintensification by identifying/resecting the primary, as illustrated by Hatten et al 26 Sixty-seven percent of their CUP patients thus avoided chemotherapy and 25% avoided RT, thus reducing the risk of long-term dysphagia, carotid atherosclerosis, and xerostomia in a relatively young patient group. 26,27 Looking at all primarily treated SCC patients in our cohort, adjuvant (C)RT could be avoided in 48.9% of patients (treated with Xi-TORS only).…”
Section: Discussionmentioning
confidence: 99%
“…In several trials, the identification rate has increased with the addition of TORS and TLM-assisted lingual mucosectomy compared to traditional diagnostic approaches [ 5 , 9 , 34 , 112 ]. The TORS procedure also allows for complete surgical, oncologic lingual mucosectomy with negative margins in 60–80% of the cases [ 87 , 88 ]. One ongoing study from Canada is pursuing the successful identification of SCCUP with TORS among T0, N1-N3, and M0 patients and possible de-intensified adjuvant RT therapy (NCT03281499) but could be limited by its small sample size ( n = 22) and recruitment not limited by HPV status, yet similar designs should be implemented as a research purpose at multiple institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of TORS and TLM-assisted lingual mucosectomy has also been proven as a new diagnostic modality for SCCUP patients, with successful identification rates of 70–78% of the primary tumor sites [ 34 , 86 , 87 , 88 ]. These diagnostic modalities provide improved visualization and access to an anatomically complex area, and freedom of movement compared to conventional surgical techniques when resecting the superficial part of the tongue base [ 34 ], and are therefore advancing as essential diagnostic tools in SCCUP.…”
Section: Identification Of the Primary Tumor Site Addressing Hpvmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of clear margins of the index tumour and limited nodal involvement (single node without extracapsular spread), surveillance is sufficient.In this group of relatively young patients, toxicity reduction is key to prevent xerostomia, dysphagia, carotid artery atherosclerosis and risk reduction for a radiotherapy-induced tumour. The introduction of TORS has improved the accessibility for oropharyngeal resection and has also taken its role in the unknown primary setting by means of tongue base mucosectomy increasing the identification rate from 40% to 80%(van Weert et al, 2020). Because of possible primary avoidance of toxicity, HPV + OPSCC patients can benefit from (adjuvant)(chemo)radiation in case of locoregional failure.…”
mentioning
confidence: 99%